Neural correlates and determinants of approach-avoidance conflict in the prelimbic prefrontal cortex - Fernandez Leon, Jose Alberto (2021)
The recollection of environmental cues associated with threat or reward allows animals to select the most appropriate behavioral responses. Neurons in the prelimbic cortex (PL) respond to both threat-and reward-associated cues. However, it remains unknown whether PL regulates threat-avoidance vs. reward-approaching responses when an animals’ decision depends on previously associated memories. Using a conflict model in which male Long-Evans rats retrieve memories of shock and food-paired cues, we observed two distinct phenotypes during conflict: I) rats that continued to press a lever for food (Pressers); and ii) rats that exhibited a complete suppression in food seeking (Non-pressers). Single-unit recordings revealed that increased risk-taking behavior in Pressers is associated with persistent food-cue responses in PL, and reduced spontaneous activity in PL glutamatergic (PLGLUT) neurons during conflict. Activating PLGLUT neurons in Pressers attenuated foodseeking responses in a neutral context, whereas inhibiting PLGLUT neurons in Non pressers reduced defensive responses and increased food approaching during conflict. Our results establish a causal role for PLGLUT neurons in mediating individual variability in memory-based risky decision making by regulating threat-avoidance vs. reward-approach behaviors.